Pengungkapan Perubahan Iklim dalam Laporan Keberlanjutan PT Unilever Indonesia Tbk 2023 - Sa'diyah, Shofiatus (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This article aims to analyze the application of the 2021 GRI Standards in uncovering issues related to climate change in the 2023 PT Unilever Indonesia Tbk poverty report through qualitative methods. The analysis focuses on aspects of greenhouse gas emissions, energy consumption, and mitigation initiatives, with document analysis as the main technique, referring to the GRI 302 (energy) and GRI 305 (emissions) guidelines. The results reveal that PT Unilever Indonesia Tbk shows a high commitment to desire and transparency in spreading climate change through achieving an 89.45% reduction in greenhouse gas emissions since 2015. Energy efficiency efforts, innovation in production processes, and various mitigation actions taken reflect the level of awareness strong environment. Although there are still obstacles in reporting emissions data indirectly (Scope 3), companies show that the poverty aspect has become a main element in business strategies in dealing with climate change.